نقد الأدب لأبي هلال العسكري في كتابه الصناعتين / Criticism of literature by Abu Hilal al-Askari in his book “al-Sana’atain” - Yaqin, Moh. Ainul (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
يمثل عنوان البحث – نقد الأدب لأبي هلال العسكري في كتابه المعنون بـ "كتاب الصناعتين – للكتابة والشعر"، وأهم شيء مما يتعلق بالناطقين بالعربية هو عدم إلمامهم بالعصور الأدبية، فالكتابة وكل ما يتعلق بها في شكل الشعر، وفي الشعر وما دار حوله من معان وألفاظ كانتا الهم الأول للأدباء والشعراء والكتاب. تناولت في مقدمة البحث الأسباب التي دعت لدراسة الموضوع، كما تعرضت فيها إلى ما جاء من حديث لأبي هلال العسكري عن تعريف البلاغة والفصاحة، وتركيزه عليهما لأنهما من أحق العلوم بالتعليم، وأولاهما بالتحفظ. فتحدثت عن آراء النقاد حول النقد وتعريفه، وحالة النقد قبل عصر أبي هلال العسكري وفي عصره، كما وضحت أن أبا هلال قد اعتمد في وضع كتابه على التقسيم والتقنين، والمنهج الذي اتبعته في بحثي هو المنهج الوصفي التاريخي التحليلي. قسمت البحث إلى أربعة فصول، تحدثت أولا عن رأيه في الشعر وأغراضه، ومفهوم النقد الأدبي وقضية اللفظ والمعنى وقضية السرقات الشعر. ناقش رأيه عن الشعر وأغراضه بينه وبين رأي النقاد الآخري، وناقش عن مفهومه عن النقد الأدب، وقضاياه النقدية في الشعر وحسن الأخذ وقبحه ونقده فيه، وأخيرا تعارضت لمقاييسه البلاغية ومباحثها عنده وأثرها فيمن بعده. الكلمات المفتاحية: أبو هلال العسكري؛ كتاب الصناعتين؛ نقد الأدب Abstract This study's title is The most important thing that concerns Arab speakers in each era, according to Abu Hilal Al-Literary Askari's Criticism in the Book of As-Shina'atain, is their ignorance. They write everything about themselves in the form of poetry. The meaning and set of words become the first concern of literati, poets, and writers in poetry. This research invites the reader to study the importance of Balaghah and Fashahah, initiated by Abu Hilal Al-Askari in his book As-Shina'atain because both are worthy of study. First, Al-Askari responded to the opinions of critics about literary criticism and its definition; second, he talked about the state of literary criticism before the era of Abu Hilal Al-Askari. The researcher also explained that Abu Hilal Al-Askari adopted two things to develop his book, i.e., division and rationalization. In this study, researchers used a historical-analytical descriptive approach. The study is divided into four chapters, the first discussing Al-Askari's opinion of poetry as well as its purpose. Second, is the concept of Al-Askari's literary criticism. Third, regarding pronunciation and meaning; fourth, regarding the theft of poetry. The first section of Al-Askari discusses poetry and its purpose with other critics. The second part discusses the concept of Arabic literature as well as critical issues about the good and bad of a poem. The last part discusses Al-Askari's rhetorical standards and their influence.